Composite carbon source-based hard carbon material, preparation method and application thereof
Patent Information
- Application Number
- CN202611420951.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-20
AI Technical Summary
目前闭孔构建方法主要分为模板法和活化后处理法:模板法如硬模板SiO2或软模板表面活性剂虽可精确调控孔道尺寸,但模板去除过程繁琐、成本高且易引入杂质,不适用于规模化生产(Journalof Energy Storage, 2026, 176: 123539);活化后处理法通常采用CO2、水蒸气或KOH等活化剂对碳材料进行刻蚀形成开放性孔隙,再通过高温热处理使表面开孔闭合转化为闭孔(Carbon, 2022, 196: 365-374)
[0039]1、本发明利用木质素焦刚性芳香网络作为“骨架支撑体”,提供抗石墨化的刚性锚点与丰富的含氧缺陷位;利用高粘结指数粘结性煤作为“反应桥连体”,利用其热解过程中产生的塑性中间相渗透并桥接不同碳源界面,诱导原位化学交联;利用液态沥青作为“流动态胶结体”,发挥其高流动性、高碳纯度特性,浸润粉体间隙并填充骨架孔隙。三者通过“刚-柔-桥”分子级协同,在热解过程中原位构筑三维共价交联网络。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage electrode material preparation technology, specifically involving a hard carbon material using lignin pyrolysis coke, asphalt and high-cohesion-index caking coal as ternary composite carbon sources, as well as a segmented pyrolysis activation preparation method. It also relates to the industrial application of this hard carbon material as a negative electrode material in sodium-ion batteries, which is applicable to the preparation and production of core electrode materials for sodium-ion batteries in various scenarios such as large-scale grid energy storage and new energy equipment energy storage. Background Technology
[0002] With the accelerated transformation of the global energy structure and the rapid expansion of the large-scale energy storage market, lithium-ion batteries, constrained by limited lithium resources, uneven distribution, and high costs, are finding it increasingly difficult to meet the urgent demands for economic efficiency and sustainability in long-term energy storage scenarios. Sodium-ion batteries, with their abundant and widely distributed sodium resources, low raw material costs, and suitability for diverse energy storage scenarios such as grid energy storage and new energy transportation, have become one of the most promising technologies for large-scale energy storage.
[0003] Due to the limitations of sodium ion physicochemical properties, graphite anodes widely used in lithium-ion battery systems cannot be directly adapted to sodium-ion battery systems. Sodium ions have a radius of 0.102 nm, approximately 34% larger than lithium ions' 0.076 nm. The narrow interplanar spacing of traditional commercial graphite anodes cannot support the reversible insertion and extraction of large-sized sodium ions. Forced insertion of sodium ions into the graphite interlayers easily leads to carbon layer structure collapse and layered framework pulverization, resulting in extremely poor battery charge-discharge cycle stability and the inability to form a stable electrochemical sodium storage system. Therefore, developing novel anode materials adapted to the characteristics of sodium ions is a core key to promoting the industrialization of sodium-ion batteries.
[0004] Hard carbon materials have structural characteristics such as high carbon skeleton disorder, large inter-crystal spacing and rich pore structure, which can effectively meet the migration and storage requirements of large-sized sodium ions. They are currently the most mainstream and most promising anode materials in the field of sodium-ion batteries.
[0005] The sodium storage mechanism of hard carbon mainly follows an "adsorption-intercalation-pore filling" model: during charge and discharge, the capacity ramp region is mainly contributed by the physical adsorption of sodium ions on the hard carbon surface, while the low-potential, high-capacity plateau region depends on the intercalation and deintercalation behavior of sodium ions between carbon microcrystal layers, and the reversible filling behavior of quasi-metallic sodium clusters within closed pores. Among these, the carbon microcrystal d... 002 The interplanar spacing directly determines the sodium ion insertion / extraction kinetics efficiency and rate performance. The closed-pore structure is the key site for improving sodium storage capacity and first coulombic efficiency. The synergistic regulation of the two is the core of optimizing the comprehensive electrochemical performance of hard carbon anode.
[0006] The microstructure and electrochemical performance of hard carbon materials are highly dependent on the type of precursor carbon source and the heat treatment process. Currently, the main carbon sources for hard carbon preparation include lignin, resin, pitch, and coal-based precursors. However, single carbon source systems are limited by their inherent molecular composition and thermochemical behavior, and none can achieve optimal performance.
[0007] Lignin-based hard carbon has a strong tendency to not be graphitized, but its inherent disordered structure and numerous defects hinder electron transport, resulting in poor electrical conductivity and severe performance degradation under high-current charge-discharge conditions (Polymers, 2025, 17(20): 2801). Pitch-based hard carbon has high carbon purity and excellent electrical conductivity, but its abundant polycyclic aromatic hydrocarbon molecules are prone to strong π-π stacking during high-temperature carbonization, inducing aromatic condensation and molecular rearrangement, tending towards graphitization. 002 Low interplanar spacing severely restricts sodium ion insertion and extraction behavior, resulting in a significant decrease in sodium storage capacity (ACS Nano, 2026, 20(9): 7988–7999). Coal-based hard carbon has high carbon production rate and significant cost advantage, but conventional heat treatment processes are prone to excessive graphitization, resulting in problems such as insufficient interplanar spacing and lack of closed pore development, which limits sodium storage capacity and cycle stability (Engineering Journal, 2024, 493,152389).
[0008] Overall, single carbon sources are constrained by molecular structure and thermal evolution behavior, and generally suffer from the technical shortcoming that the microcrystalline structure and pore structure cannot be optimized in a coordinated manner, making it difficult to simultaneously achieve the performance requirements of high capacity, high first efficiency, and high cycle stability.
[0009] To overcome the performance limitations of a single carbon source, existing technologies generally adopt a multi-carbon source composite modification strategy. By utilizing the structural advantages of different carbon sources and complementing each other through molecular-level matching and thermal evolution behavior, the degree of graphitization and pore structure of hard carbon can be controlled to improve sodium storage performance.
[0010] In composite carbon source modification systems, the construction of three-dimensional cross-linked carbon networks is crucial for suppressing hard carbon graphitization and stabilizing the microstructure. However, in existing technologies, systems such as lignin / resin blends with pitch and coal co-pyrolysis with polymers often form macroscopic phase separation or locally excessive graphitization regions, resulting in poor carbon network uniformity. The cross-linked networks are mostly formed through physical blending, with insufficient chemical cross-linking, making it difficult to maintain framework stability during subsequent high-temperature treatments and limiting the effectiveness of graphitization suppression (Chemical Engineering Journal, 2025, 506: 159968). Furthermore, mixed carbon sources have poor formability, and the framework easily collapses during heat treatment, with a large number of original pores closing and disappearing. This fails to provide sufficient pore precursors for subsequent activation and closed-pore transformation, thus failing to fully leverage the synergistic cross-linking effect of multi-component, multi-scale carbon source systems during pyrolysis and their regulatory role in the evolution path of carbon microcrystals and pore structures.
[0011] Effective construction of closed-pore structures is key to improving the capacity and first coulombic efficiency of hard carbon platforms. Currently, closed-pore construction methods are mainly divided into template methods and activation post-treatment methods: Template methods, such as hard templates (SiO2) or soft templates (surfactants), can precisely control pore size, but the template removal process is cumbersome, costly, and prone to introducing impurities, making it unsuitable for large-scale production (Journal of Energy Storage, 2026, 176: 123539); Activation post-treatment methods typically use activators such as CO2, steam, or KOH to etch open pores into carbon materials, and then use high-temperature heat treatment to close the surface open pores and transform them into closed pores (Carbon, 2022, 196: 365-374).
[0012] Most existing closed-pore construction strategies target single carbon source systems, failing to consider the impact of differences in the thermal evolution behavior of multiple components in composite carbon sources on closed-pore formation. Furthermore, the lack of synergistic design between activation and carbonization processes and the precursor cross-linking structure leads to limited closed-pore conversion efficiency, inhomogeneous closed-pore structures, and limited improvement in sodium storage platform capacity. Therefore, organically integrating the molecular cross-linking effect of multi-component carbon sources with the pore structure evolution path of CO2 activation-high-temperature carbonization, and simultaneously addressing the problems of graphitization inhibition and closed-pore enrichment through a staged synergistic regulation strategy, is of significant technical necessity. This invention is proposed to address this need. Summary of the Invention
[0013] Given the current state of the prior art, especially regarding the use of existing hard carbon materials as the anode in sodium-ion batteries, the interplanar spacing (d) of the carbon crystals... 002The difficulty in synergistic optimization between the graphitized and closed-cell structures leads to a structural bottleneck: limited sodium ion intercalation / deintercalation kinetics, low plateau capacity and initial coulombic efficiency, resulting in overall electrochemical performance failing to meet application requirements. This invention, based on in-depth and extensive research in the field of hard carbon materials, has discovered that a ternary composite carbon source system—combining industrial waste lignin pyrolysis coke, liquid asphalt, and high-adhesion-index cohesive coal—with a phased synergistic control strategy of "low-temperature pre-forming pyrolysis to construct a three-dimensional cross-linked network, CO2-directed activation to construct primary open pores, and ultra-high-temperature deep carbonization to achieve closed-cell conversion," can stepwise solve the core technical problems of excessive graphitization, small interplanar spacing, and lack of closed pores in hard carbon materials. This invention is based on the above findings.
[0014] Therefore, one objective of this invention is to provide a method for preparing composite carbon source-based hard carbon materials. The method innovatively employs a ternary composite carbon source system of "asphalt-lignin coke prepared by pyrolysis of industrial waste lignin-high bonding index caking coal," combined with a phased synergistic regulation of carbon crystal interplanar spacing and closed-pore structure through "low-temperature pre-forming pyrolysis to construct a three-dimensional cross-linked network-CO2 directional activation to construct native open pores-ultra-high temperature deep carbonization to achieve closed-pore transformation."
[0015] The second objective of this invention is to provide a composite carbon-based hard carbon material prepared by the above-mentioned preparation method. This hard carbon material has high reversible capacity, excellent first-cycle coulombic efficiency, and good cycle stability. At the same time, it realizes the efficient utilization of industrial solid waste resources and reduces preparation costs. This is of great significance for promoting the green industrialization and large-scale energy storage application of sodium-ion batteries.
[0016] The third objective of this invention is to provide a composite carbon-based hard carbon material prepared by the above-described method for use as a negative electrode material in sodium-ion batteries.
[0017] The technical solution for achieving the above-mentioned objectives can be summarized as follows:
[0018] A method for preparing a composite carbon-based hard carbon material includes the following steps:
[0019] The lignin coke and pitch obtained from lignin pyrolysis are uniformly compounded with caking coal with a high bonding index, and then subjected to stepwise treatments of pressurized pre-forming pyrolysis, CO2 activation and ultra-high temperature deep carbonization to prepare composite carbon source-based hard carbon materials.
[0020] According to the present invention, preferably, the lignin is industrial waste gas lignin, and more preferably at least one of papermaking black liquor purified lignin and biorefining waste residue lignin;
[0021] The asphalt is liquid asphalt, and more preferably at least one of liquid coal tar pitch and liquid petroleum asphalt;
[0022] The caking coal with a high caking index is preferably coking coal with a caking index of 75 to 85.
[0023] According to the present invention, preferably, the lignin pyrolysis process is as follows: the lignin is crushed and pyrolyzed at 400-600 °C for 1-2 h to obtain lignin char.
[0024] According to the present invention, preferably, the lignin coke and caking coal are pulverized and then deashed before being compounded. Preferably, the lignin coke and caking coal are pulverized separately and screened for particle size less than 0.15 mm before use. Preferably, the deashing process involves acid washing the pulverized lignin coke and caking coal in a mixed solution of hydrofluoric acid and hydrochloric acid to remove inorganic impurities and ash. Preferably, the deashed lignin coke is thoroughly kneaded with the deashed caking coal at a ratio of 10-30 wt% to obtain a mixture.
[0025] According to the present invention, preferably, the amount of asphalt added is controlled at 10 to 15 wt% of the mass of the mixture, and more preferably, the ash content of the asphalt is less than 0.05 wt%.
[0026] According to the present invention, lignin coke, pitch and caking coal are thoroughly mixed and then subjected to pressure preforming pyrolysis.
[0027] According to the present invention, preferably, the pressure preforming pyrolysis process is as follows: pressing and molding under a pressure of 5-7 MPa to obtain molding raw material, heating the molding raw material to 400-500 ℃ at a heating rate of 0.5-1.5 ℃ / min, and pyrolyzing at a constant temperature for 1.5-2 h to obtain molding carbon material.
[0028] According to the present invention, preferably, the shaped carbon material is heated to 800-850 °C at a heating rate of 2-5 °C / min under an inert atmosphere, and activated by introducing CO2 with a volume fraction of 55%.
[0029] According to the present invention, preferably, the ultra-high temperature deep carbonization treatment is performed by heating to 1400 °C at a heating rate of 1–3 °C / min under an inert atmosphere for 2–3 h.
[0030] According to a preferred embodiment of the present invention, the preparation method of the composite carbon source-based hard carbon material includes the following steps:
[0031] (1) Crush the lignin and pyrolyze it at 400-600 °C for 1-2 h to prepare lignin char;
[0032] (2) The lignin coke and the caking coal with a high caking index are crushed separately and screened with a particle size of less than 0.15 mm. They are then acid-washed in a mixed solution of hydrofluoric acid and hydrochloric acid to remove inorganic impurities and ash. The deashed lignin coke is fully kneaded with the deashed caking coal at a ratio of 10-30 wt% to obtain a mixture.
[0033] (3) The mixture is fully kneaded and moistened with liquid asphalt, and then pressed into shape under a pressure of 5-7 MPa to obtain the molding raw material;
[0034] (4) Under air-isolated conditions, the molding raw material is subjected to a temperature of 800–1200 N / m. 2 Under pressure, the temperature is raised to 400-500 ℃ and pyrolyzed for 1-2 h to prepare shaped carbon materials;
[0035] (5) The shaped carbon material is heated to 800-850°C in an inert atmosphere, CO2 is introduced for activation treatment, and after activation, it is naturally cooled to room temperature in an inert atmosphere, and then heated to 1400°C for ultra-high temperature deep carbonization to achieve controllable conversion from open pores to closed pores, and finally obtain composite carbon source-based hard carbon material.
[0036] The present invention also provides composite carbon source-based hard carbon materials prepared by the above method.
[0037] The present invention also provides the application of the above-mentioned composite carbon source-based hard carbon material as a negative electrode material in sodium-ion batteries.
[0038] The beneficial effects of this invention are as follows:
[0039] 1. This invention utilizes a rigid aromatic network of lignin coke as a "skeleton support," providing rigid anchor points and abundant oxygen-containing defect sites to resist graphitization; it utilizes high-cohesion-index caking coal as a "reactive bridge," leveraging the plastic mesophase generated during pyrolysis to permeate and bridge different carbon source interfaces, inducing in-situ chemical cross-linking; and it utilizes liquid asphalt as a "fluid dynamic binder," leveraging its high fluidity and high carbon purity to wet powder gaps and fill skeleton pores. Through a "rigid-flexible-bridge" molecular-level synergy, these three components in-situ construct a three-dimensional covalent cross-linked network during pyrolysis.
[0040] 2. This invention constructs a molecular-level chemical crosslinking system of a ternary composite carbon source consisting of "asphalt-lignin coke-high caking index caking coal," coupled with a staged synergistic control strategy of "low-temperature pressure pre-forming pyrolysis-CO2 directional activation-ultra-high temperature deep carbonization," thereby achieving control over the interplanar spacing (d) of carbon crystals in hard carbon materials. 002 The efficient synergistic regulation of disorder and closed-pore characteristics was achieved. The resulting composite carbon-based hard carbon material possesses a highly disordered random-layer carbon structure, significantly expanded carbon layer interplanar spacing, and an ultra-high content of closed-pore structure. 002The wavelength can reach above 0.370 nm, and the closed-pore volume can reach 0.13 cm³. 3 / g or more.
[0041] 3. This invention utilizes the difference in gasification reactivity of composite carbon sources to pre-construct a uniformly distributed primary open-pore structure in the shaped carbon material through CO2 activation. Then, through ultra-high temperature carbonization treatment, it achieves efficient conversion of open pores into closed pores, providing sufficient space for sodium ion "pore filling" sodium storage behavior, significantly improving the capacity of the low potential plateau region, while effectively suppressing irreversible sodium loss of the SEI film and improving the first-cycle coulombic efficiency.
[0042] 4. When the composite carbon source-based hard carbon material of the present invention is used as a negative electrode material for sodium-ion batteries, it can simultaneously achieve high reversible specific capacity (391.7), high initial coulombic efficiency (94.0) and excellent cycle stability (93.1), and its comprehensive performance is significantly better than that of traditional asphalt, coal-based and lignin-based hard carbon materials. Attached Figure Description
[0043] Figure 1 The XRD patterns of the composite carbon source-based hard carbon materials prepared in Examples 1-3 and Comparative Examples 1-3 are shown.
[0044] Figure 2 SEM and TEM images of the composite carbon source-based hard carbon material prepared in Example 1.
[0045] Figure 3 The closed-cell volume of pitch-based hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-4 was determined.
[0046] Figure 4 The first charge-discharge specific capacity curve of the composite carbon source-based hard carbon material prepared in Example 1. Detailed Implementation
[0047] This invention provides a composite carbon source-based hard carbon material, its preparation method, and its application. The core lies in the molecular-level synergistic formulation of a ternary composite carbon source system of "asphalt-lignin coke-high bonding index caking coal" and the organic connection of a three-stage heat treatment process of "low temperature pressure preforming pyrolysis-CO2 directional activation-ultra-high temperature deep carbonization", thereby achieving precise control over the evolution path of hard carbon microcrystalline structure and the evolution process of pore structure.
[0048] The preparation method of the composite carbon source-based hard carbon material of the present invention includes the following steps:
[0049] A composite carbon-based hard carbon material was prepared by uniformly compounding lignin coke and pitch obtained from lignin pyrolysis with caking coal having a high caking index, followed by stepwise treatment of pressurized pre-forming pyrolysis, CO2 activation, and ultra-high temperature deep carbonization. This hard carbon material can be used as a negative electrode for high-performance sodium-ion batteries.
[0050] According to this invention, the lignin used as raw material can be industrial waste lignin, enabling efficient utilization of industrial solid waste resources and reducing preparation costs. The rigid aromatic network of lignin coke is used as a "skeleton support," providing rigid anchor points against graphitization and abundant oxygen-containing defect sites. The caking coal used is high-caking-index caking coal, which serves as a "reactive bridge," utilizing the plastic mesophase generated during pyrolysis to permeate and bridge different carbon source interfaces, inducing in-situ chemical cross-linking. The asphalt used can be liquid asphalt, which acts as a "fluid dynamic binder," leveraging its high fluidity and high carbon purity to wet powder gaps and fill skeleton pores. A three-dimensional covalent cross-linked network is constructed in-situ during pyrolysis. These three components inhibit graphitization through a "rigid-flexible-bridge" molecular-level synergistic effect, achieving simultaneous optimization of carbon interlayer spacing and closed-pore structure.
[0051] In one or more preferred embodiments, the lignin is preferably lignin purified from papermaking black liquor, lignin from biorefining waste residue, or other industrial by-product waste lignin; the bitumen is preferably at least one of liquid coal tar pitch or liquid petroleum bitumen; and the caking coal with a high caking index is preferably coking coal with a caking index of 75 to 85.
[0052] According to the present invention, lignin is pyrolyzed to obtain lignin char. Preferably, the lignin is crushed and pyrolyzed at 400–600 °C for 1–2 h to obtain lignin char.
[0053] According to the present invention, lignin coke and caking coal are preferably crushed and deashed before being compounded.
[0054] In one or more preferred embodiments, the lignin coke and caking coal are respectively pulverized and screened for particle size less than 0.15 mm for use. Preferably, the deashing process is as follows: the pulverized lignin coke and caking coal are acid-washed in a mixed solution of hydrofluoric acid and hydrochloric acid to remove inorganic impurities and ash.
[0055] In one or more preferred embodiments, the deashed lignin coke is fully kneaded with deashed caking coal at a ratio of 10-30 wt% to obtain a mixture.
[0056] In one or more preferred embodiments, the amount of liquid asphalt added is controlled at 10 to 15 wt% of the mass of the mixture, and more preferably, the ash content of the liquid asphalt is less than 0.05 wt%.
[0057] According to the present invention, lignin coke, pitch and caking coal are thoroughly mixed and then subjected to pressure preforming pyrolysis.
[0058] In one or more preferred embodiments, the material is pressed and molded under a pressure of 5–7 MPa to obtain the molding raw material. Preferably, the molding raw material is heated to 400–500 °C at a heating rate of 0.5–1.5 °C / min and pyrolyzed at a constant temperature for 1.5–2 h to obtain the molded carbon material. This ensures that the lignin coke, pitch, and caking coal are fully cross-linked, avoiding problems such as skeleton cracking and phase separation caused by rapid heating.
[0059] According to the present invention, CO2 activation is performed after pressurized preforming pyrolysis.
[0060] In one or more preferred embodiments, the shaped carbon material is heated to 800-850°C at a heating rate of 2-5°C / min under an inert atmosphere, and activated by introducing CO2 with a volume fraction of 55%. After activation, the sample is allowed to cool naturally to room temperature in an inert atmosphere. The activation time is preferably 1-3 hours, and the inert atmosphere can be nitrogen, argon, etc.
[0061] According to the present invention, after the CO2 activation treatment is completed, an ultra-high temperature deep carbonization treatment is performed.
[0062] In one or more preferred embodiments, the ultra-high temperature deep carbonization treatment is performed by heating to 1400 °C at a heating rate of 1–3 °C / min under an inert atmosphere for 2–3 h.
[0063] According to the present invention, a preferred embodiment of the method for preparing the composite carbon source-based hard carbon material includes the following steps:
[0064] (1) Crush the lignin and pyrolyze it at 400-600 °C for 1-2 h to prepare lignin char;
[0065] (2) The lignin coke and the caking coal with a high caking index are crushed separately and screened with a particle size of less than 0.15 mm. They are then acid-washed in a mixed solution of hydrofluoric acid and hydrochloric acid to remove inorganic impurities and ash. The deashed lignin coke is fully kneaded with the deashed caking coal at a ratio of 10-30 wt% to obtain a mixture.
[0066] (3) The mixture is fully kneaded and moistened with liquid asphalt, and then pressed into shape under a pressure of 5-7 MPa to obtain the molding raw material;
[0067] (4) Under air-isolated conditions, the molding raw material is subjected to a temperature of 800–1200 N / m. 2 Under pressure, the temperature is raised to 400-500 ℃ and pyrolyzed for 1-2 h to prepare shaped carbon materials;
[0068] (5) The shaped carbon material is heated to 800-850°C in an inert atmosphere, CO2 is introduced for activation treatment, and after activation, it is naturally cooled to room temperature in an inert atmosphere, and then heated to 1400°C for ultra-high temperature deep carbonization to achieve controllable conversion from open pores to closed pores, and finally obtain composite carbon source-based hard carbon material.
[0069] The present invention also provides composite carbon source-based hard carbon materials prepared by the above method.
[0070] The present invention also provides the application of the above-mentioned composite carbon source-based hard carbon material as a negative electrode material in sodium-ion batteries.
[0071] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, so that those skilled in the art can better understand and utilize the present invention, and are not intended to limit the scope of protection of the present invention.
[0072] The experimental methods, production processes, instruments, and equipment involved in the embodiments and comparative examples of this invention are all conventional names in the art, and are very clear and distinct in their respective fields of application. Those skilled in the art can understand the conventional process steps and apply the corresponding equipment based on these names, and implement them according to conventional conditions or conditions recommended by the manufacturer.
[0073] The raw materials or reagents used in the embodiments and comparative examples of this invention are not subject to any special restrictions on their source; they are all conventional products that can be purchased commercially. They can also be prepared according to conventional methods well known to those skilled in the art. The room temperature described in this invention is 25℃±5℃.
[0074] Example 1
[0075] The preparation of composite carbon source-based hard carbon materials includes the following steps:
[0076] (1) Take waste lignin from the purification of industrial papermaking black liquor as raw material, crush it and place it in a tube furnace, heat it to 600 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 2 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0077] (2) The lignin coke and coking coal with a bonding index G value of 85 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 25 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:2. The mixture was stirred and acid washed for 4 h in a water bath at 70 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0078] (3) Add 12 wt% of liquid coal tar pitch (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly until the material is uniformly wetted, then place it in a mold and press it under 6 MPa pressure to obtain the molding raw material.
[0079] (4) The molding raw material is placed in a muffle furnace, and under nitrogen protection, a surface pressure of 1000 N / m² is applied. The material is heated to 450 °C at a heating rate of 1.0 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0080] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 800 ℃ at a heating rate of 4 ℃ / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the sample was activated at a constant temperature for 2 h. After activation, the nitrogen atmosphere was switched back and the sample was allowed to cool naturally to room temperature. Subsequently, the sample was heated to 1400 ℃ at a heating rate of 2 ℃ / min under a nitrogen atmosphere and carbonized at a constant temperature for 3 h. After natural cooling to room temperature, the composite carbon source-based hard carbon material was obtained and named CBA-1.
[0081] Example 2
[0082] The preparation of composite carbon source-based hard carbon materials includes the following steps:
[0083] (1) Take lignin waste from biorefining industry as raw material, place it in a tube furnace, heat it to 550 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 2 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0084] (2) The lignin coke and coking coal with a bonding index G value of 85 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 20 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:1. The mixture was stirred and acid washed for 3 h in a water bath at 80 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0085] (3) Add 15 wt% of liquid coal tar pitch (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly, and then press it into shape under a pressure of 7 MPa to obtain the molding raw material.
[0086] (4) The molding raw material is placed in an atmosphere furnace, and under nitrogen protection, a surface pressure of 1200 N / m² is applied. The material is heated to 480 °C at a heating rate of 1.5 °C / min, and pyrolyzed at a constant temperature for 1.5 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0087] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 850 °C at a heating rate of 5 °C / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the material was activated at a constant temperature for 1.5 h. After activation, the atmosphere was switched back to nitrogen and the material was allowed to cool naturally to room temperature. Subsequently, the material was heated to 1400 °C at a heating rate of 1.5 °C / min under a nitrogen atmosphere and carbonized at a constant temperature for 3 h. The material was then allowed to cool naturally to room temperature to obtain the composite carbon source-based hard carbon material, named CBA-2.
[0088] Example 3
[0089] The preparation of composite carbon source-based hard carbon materials includes the following steps:
[0090] (1) Take lignin waste from biorefining industry as raw material, place it in a tube furnace, heat it to 550 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 1.5 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0091] (2) The lignin coke and coking coal with a bonding index G value of 80 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 30 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:3. The mixture was stirred and acid washed for 6 h in a water bath at 60 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0092] (3) Add 10 wt% of liquid petroleum asphalt (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly, and then press it into shape under a pressure of 5 MPa to obtain the molding raw material.
[0093] (4) The molding raw material is placed in an atmosphere furnace, and under nitrogen protection, a surface pressure of 900 N / m² is applied. The material is heated to 420 °C at a heating rate of 0.5 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0094] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 820 °C at a heating rate of 3 °C / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the material was activated at a constant temperature for 2.5 h. After activation, the atmosphere was switched back to nitrogen and the material was allowed to cool naturally to room temperature. Subsequently, the material was heated to 1400 °C at a heating rate of 2.5 °C / min under a nitrogen atmosphere and carbonized at a constant temperature for 2.5 h. The material was then allowed to cool naturally to room temperature to obtain the composite carbon source-based hard carbon material, named CBA-3.
[0095] Example 4
[0096] The preparation of composite carbon source-based hard carbon materials includes the following steps:
[0097] (1) Take waste lignin from the purification of industrial papermaking black liquor as raw material, crush it and place it in a tube furnace, heat it to 500 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 1.5 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0098] (2) The lignin coke and coking coal with a bonding index G value of 75 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 20 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:2. The mixture was stirred and acid washed for 4 h in a water bath at 70 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0099] (3) Add 15 wt% of liquid petroleum asphalt (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly until the material is uniformly wetted, then place it in a mold and press it under 7 MPa pressure to obtain the molding raw material.
[0100] (4) The molding raw material is placed in a muffle furnace, and under nitrogen protection, a surface pressure of 1200 N / m² is applied. The material is heated to 480 °C at a heating rate of 1.5 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0101] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 850 °C at a heating rate of 5 °C / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the sample was activated at a constant temperature for 2 h. After activation, the nitrogen atmosphere was switched back and the sample was allowed to cool naturally to room temperature. Subsequently, the sample was heated to 1400 °C at a heating rate of 3 °C / min under a nitrogen atmosphere and carbonized at a constant temperature for 2 h. After cooling naturally to room temperature, the composite carbon source-based hard carbon material was obtained and named CBA-4.
[0102] Comparative Example 1
[0103] (1) The coking coal with a bonding index G value of 85 was crushed and sieved to a particle size of <0.15 mm. It was placed in a mixed acid solution with a volume ratio of hydrofluoric acid and hydrochloric acid of 1:2 and stirred and acid-washed for 4 h under a water bath at 80 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0104] (2) Add 10 wt% of liquid coal tar pitch (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly until the material is uniformly wetted, then place it in a mold and press it into shape under a pressure of 6.5 MPa to obtain the molding raw material.
[0105] (3) The molding raw material is placed in a muffle furnace, and under nitrogen protection, a surface pressure of 1200 N / m² is applied. The material is heated to 450 °C at a heating rate of 1.0 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0106] (4) The shaped carbon material was placed in a high-temperature tube furnace and heated to 800 ℃ at a heating rate of 4 ℃ / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the sample was activated at a constant temperature for 2 h. After activation, the nitrogen atmosphere was switched back and the sample was allowed to cool naturally to room temperature. Subsequently, the sample was heated to 1400 ℃ at a heating rate of 2 ℃ / min under a nitrogen atmosphere and carbonized at a constant temperature for 3 h. After cooling naturally to room temperature, the composite carbon source-based hard carbon material was obtained and named HCM-1.
[0107] Comparative Example 2
[0108] (1) Take waste lignin from the purification of industrial papermaking black liquor as raw material, crush it and place it in a tube furnace, heat it to 600 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 1.5 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0109] (2) Place the lignin char in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:2, stir and acid wash for 4 h under a water bath at 70 ℃, then wash with deionized water until the filtrate is neutral, and dry at 105 ℃ for 12 h to obtain the deashed mixture.
[0110] (3) Add 15 wt% of liquid petroleum asphalt (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly until the material is uniformly wetted, then place it in a mold and press it under 7 MPa pressure to obtain the molding raw material.
[0111] (4) The molding raw material is placed in a muffle furnace, and under nitrogen protection, a surface pressure of 1200 N / m² is applied. The material is heated to 480 °C at a heating rate of 1.5 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0112] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 850 °C at a heating rate of 5 °C / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the sample was activated at a constant temperature for 2 h. After activation, the nitrogen atmosphere was switched back and the sample was allowed to cool naturally to room temperature. Subsequently, the sample was heated to 1400 °C at a heating rate of 3 °C / min under a nitrogen atmosphere and carbonized at a constant temperature for 2 h. After cooling naturally to room temperature, the composite carbon source-based hard carbon material was obtained and named HCM-2.
[0113] Comparative Example 3
[0114] (1) Take lignin waste from biorefining industry as raw material, place it in a tube furnace, heat it to 500 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 1.5 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0115] (2) The lignin coke and coking coal with a bonding index G value of 80 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 25 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:3. The mixture was stirred and acid washed for 6 h in a water bath at 60 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0116] (3) Add 10 wt% of liquid coal tar pitch (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly, and then press it into shape under a pressure of 6 MPa to obtain the molding raw material.
[0117] (5) The molding raw material was placed in a high-temperature tube furnace and heated to 820 °C at a heating rate of 3 °C / min under a nitrogen atmosphere. Then, a CO2 / N2 mixed gas with a volume fraction of 55% was introduced and the material was activated at a constant temperature for 2.5 h. After activation, the atmosphere was switched back to nitrogen and the material was allowed to cool naturally to room temperature. Subsequently, the material was heated to 1400 °C at a heating rate of 2.5 °C / min under a nitrogen atmosphere and carbonized at a constant temperature for 2.5 h. The material was then allowed to cool naturally to room temperature to obtain the composite carbon source-based hard carbon material, named HCM-3.
[0118] Comparative Example 4
[0119] (1) Take waste lignin from the purification of industrial papermaking black liquor as raw material, crush it and place it in a tube furnace, heat it to 600 ℃ at a heating rate of 5 ℃ / min under nitrogen atmosphere, keep it at a constant temperature for 2 h, and cool it naturally to room temperature to obtain lignin coke. Crush it and sieve it, and select the sieve with a particle size of less than 0.15 mm for later use.
[0120] (2) The lignin coke and coking coal with a bonding index G value of 85 were crushed and sieved to a particle size of <0.15 mm. The two were mixed at a ratio of 25 wt% lignin coke and placed in a mixed acid solution of hydrofluoric acid and hydrochloric acid in a volume ratio of 1:2. The mixture was stirred and acid washed for 4 h in a water bath at 70 ℃. Then it was washed with deionized water until the filtrate was neutral and dried at 105 ℃ for 12 h to obtain the deashed mixture.
[0121] (3) Add 12 wt% of liquid petroleum asphalt (ash content < 0.05 wt%) to the deashed mixture, knead thoroughly until the material is uniformly wetted, then place it in a mold and press it under 6 MPa pressure to obtain the molding raw material.
[0122] (4) The molding raw material is placed in a muffle furnace, and under nitrogen protection, a surface pressure of 1000 N / m² is applied. The material is heated to 450 °C at a heating rate of 1.0 °C / min, and pyrolyzed at a constant temperature for 2 h. The material is then naturally cooled to room temperature to obtain the molding carbon material.
[0123] (5) The shaped carbon material was placed in a high-temperature tube furnace and heated to 800 ℃ at a heating rate of 4 ℃ / min under a nitrogen atmosphere. After carbonization, the atmosphere was switched back to nitrogen and the sample was allowed to cool naturally to room temperature. Then, under a nitrogen atmosphere, the material was heated to 1400 ℃ at a heating rate of 2 ℃ / min and carbonized at a constant temperature for 3 h. After cooling naturally to room temperature, the composite carbon source-based hard carbon material was obtained and named HCM-4.
[0124] Comparative Example 5
[0125] Commercially available hard carbon material is named HCM-5.
[0126] Experimental Example 1
[0127] The XRD spectra of the hard carbon materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested, as shown below. Figure 1 As shown. All samples exhibit characteristic diffraction peaks corresponding to the (002) and (100) crystal planes of carbon materials near 2θ≈24° and 2θ≈43°. Compared with the comparative samples, the (002) diffraction peak of the CBA series samples of this invention is significantly shifted to lower angles, and the d-values of CBA-1, CBA-2, and CBA-3 are significantly lower. 002The interplanar spacings are 0.3810 nm, 0.3792 nm, and 0.3812 nm, respectively, while the dc of the dual carbon source comparisons HCM-1 and HCM-2 is... 002 Only 0.3511 and 0.3603, the d of CCP-9 without low-temperature preforming pyrolysis. 002 The wavelength was 0.365 nm. This result indicates that, in the low-temperature pre-forming pyrolysis stage of this invention, the plastic mesophase formed by the thermal conversion of cohesive coal acts as a reaction medium, promoting in-situ dehydrogenation condensation and cross-linking reactions between the rigid aromatic network of lignin coke and the polycyclic aromatic hydrocarbon molecules of liquid asphalt, forming a three-dimensional covalently bonded network, rather than a simple physical mixture. This molecular-level chemical cross-linking effectively inhibits sp... 2 The preferred orientation and ordered stacking of the carbon sheets significantly increased the interplanar spacing of the carbon crystals. The large interplanar spacing provides a wide channel for the rapid insertion / extraction of sodium ions, lowers the diffusion barrier, and lays the structural foundation for high plateau capacity and excellent rate performance.
[0128] Experimental Example 2
[0129] Figure 2 SEM and TEM images of the hard carbon material prepared in Test Example 1 are shown. The SEM images show that the material maintains a complete and continuous carbon matrix framework, without particle pulverization or macroscopic cracking. This indicates that during the low-temperature preforming pyrolysis process, lignin coke, caking coal, and liquid pitch form a stable three-dimensional carbon framework through chemical cross-linking, effectively suppressing structural collapse during subsequent heat treatment. Numerous interconnected open pores are distributed within the material, providing ample mass transfer channels for the CO2 activation gas, demonstrating that the cross-linked framework ensures the uniform formation of open pores during the activation stage, providing a structural precursor for subsequent closed-pore conversion. The TEM images show that the material exhibits a typical disordered layered carbon structure of hard carbon, with short-range order and long-range disorder in the carbon layers. 002 The interplanar spacing is distributed in the range of 0.37–0.39 nm, consistent with the XRD results. The nanoscale closed-pore structures marked with white circles in the figure are uniformly dispersed within the carbon matrix, confirming that the pre-built open pores by CO2 activation achieve efficient conversion to closed pores during ultra-high temperature carbonization at 1400 °C. These closed pores store sodium clusters through a pore-filling mechanism and are completely encapsulated by the carbon matrix, preventing electrolyte penetration. This significantly reduces irreversible SEI film formation and is crucial for improving the first coulombic efficiency.
[0130] Experimental Example 3
[0131] The closed-pore volume of the carbon materials prepared in Examples 1-4 and Comparative Examples 1-4 was tested, and the results are as follows: Figure 3As shown, the closed-cell volume of the CBA series is significantly higher than that of the HCM series. This result verifies the synergistic effectiveness of the three-stage process of this invention. The dual carbon sources (HCM-1 and HCM-2), and HCM-3 without low-temperature pre-forming pyrolysis, suffer from insufficient carbon skeleton cross-linking, resulting in severe structural shrinkage during high-temperature carbonization. Many open pores collapse and disappear before the pore-closing conversion, failing to form effective closed pores. HCM-4 without CO2 activation exhibits extremely low pore-closing conversion efficiency due to the lack of native open-cell precursors. This invention constructs a stable three-dimensional cross-linked carbon skeleton through low-temperature pressurized pre-forming pyrolysis, providing structural support for subsequent CO2 activation. Furthermore, through the synergistic differences in the gasification reactivity of the ternary carbon sources (lignin char reacts preferentially due to its rich oxygen-containing functional groups, while coal and bitumen components exhibit higher antioxidant stability), it achieves precise and controllable construction of open pores, ensuring uniform generation of activated open pores and controllable closure conversion during high-temperature carbonization. This results in ultra-high density enrichment of closed pores, providing ample space for sodium ion pore-filling and sodium storage behavior.
[0132] Application examples
[0133] The hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-5 were used as negative electrode active materials for sodium-ion batteries. Hard carbon materials, conductive carbon black, and sodium carboxymethyl cellulose binder were mixed at a mass ratio of 8:1:1, and an appropriate amount of deionized water was added to form a uniform slurry. This slurry was then uniformly coated onto a 15 μm thick copper foil current collector using a doctor blade coating method. After vacuum drying at 80 °C for 12 h, the slurry was rolled and punched into circular negative electrode sheets with a diameter of 12 mm. Using a sodium metal sheet as the counter electrode, a Whatman GF / D glass fiber membrane as the separator, and a 1 mol / L NaPF6 solution dissolved in diethylene glycol dimethyl ether (DIGLYME) as the electrolyte, CR2032 coin cell half-cells were assembled in a glove box filled with high-purity argon. The assembled cells were then allowed to stand at a constant temperature of 25 °C for 8 h to allow the electrolyte to fully wet the electrode materials. The electrochemical performance was tested using a Neware CT-4008T battery testing system under constant current charge-discharge conditions. The test results are summarized in Table 1. The initial charge-discharge specific capacity curve of the composite carbon-based hard carbon material prepared in Example 1 is shown in Table 1. Figure 4 As shown.
[0134] Table 1. Performance test results of Na-ion batteries in Examples 1-4 and Comparative Examples 1-4
[0135] sample Reversible capacity (mAh / g) First-week coulomb efficiency (%) 1 A / g capacity retention (%) after 500 cycles CBA-1 391.7 94.0 93.1 CBA-2 385.2 93.2 92.3 CBA-3 387.5 93.4 92.6 CBA-4 384.9 93.1 92.2 HCM-1 257.6 81.5 78.2 HCM-2 306.4 85.2 84.5 HCM-3 285.7 83.1 81.8 HCM-4 278.3 82.7 81.4 HCM-5 323.1 87.6 91.5
[0136] The reversible capacity (>385 mAh / g) of the CBA series hard carbon materials is significantly higher than that of all comparative samples, mainly due to their larger dg. 002The efficient sodium ion intercalation space provided by the interplanar spacing and the additional adsorption-filling sodium storage capacity provided by the closed-pore structure are significant advantages of the CBA series. The first-cycle coulombic efficiency (>93%) of the CBA series is also superior to the comparative sample, attributed to the high-density closed-pore structure effectively reducing direct contact between the electrolyte and the interior of the active material, inhibiting excessive formation of the irreversible SEI film, and reducing irreversible sodium consumption. After 500 cycles at a high current density of 1 A / g, the capacity retention rate of the CBA series is greater than 92%, far exceeding that of the comparative sample, fully demonstrating the effective buffering of volume changes and good maintenance of structural integrity by the material's three-dimensional cross-linked stable carbon framework and closed-pore structure.
Claims
1. A method for preparing a composite carbon source-based hard carbon material, comprising the following steps: The lignin coke and pitch obtained from lignin pyrolysis are uniformly compounded with caking coal with a high bonding index, and then subjected to stepwise treatments of pressurized pre-forming pyrolysis, CO2 activation and ultra-high temperature deep carbonization to prepare composite carbon source-based hard carbon materials.
2. The method for preparing composite carbon source-based hard carbon material according to claim 1, characterized in that, The lignin is at least one of papermaking black liquor purified lignin and biorefining waste residue lignin. The asphalt is liquid asphalt, preferably at least one of liquid coal tar pitch and liquid petroleum asphalt; The caking coal with a high caking index is coking coal with a caking index of 75 to 85.
3. The method for preparing composite carbon source-based hard carbon material according to claim 1, characterized in that, The pyrolysis process of lignin is as follows: lignin is crushed and pyrolyzed at 400-600 ℃ for 1-2 h to obtain lignin char.
4. The method for preparing composite carbon source-based hard carbon material according to claim 1, characterized in that, The lignin coke and caking coal are crushed, deashed, and then compounded. Preferably, the lignin coke and caking coal are crushed separately and screened with a particle size of less than 0.15 mm for use; Preferably, the deashing process is as follows: the pulverized lignin coke and caking coal are acid-washed in a mixed solution of hydrofluoric acid and hydrochloric acid to remove inorganic impurities and ash. Preferably, the deashed lignin coke is fully kneaded with deashed caking coal at a ratio of 10-30 wt% to obtain a mixture.
5. The method for preparing composite carbon source-based hard carbon material according to claim 4, characterized in that, The amount of asphalt added is controlled at 10-15 wt% of the mass of the mixture; preferably, the ash content of the asphalt is less than 0.05 wt%.
6. The method for preparing composite carbon source-based hard carbon material according to claim 1, characterized in that, The pressurized preforming pyrolysis process is as follows: the material is pressed and formed under a pressure of 5-7 MPa to obtain the molding raw material. The molding raw material is heated to 400-500 ℃ at a heating rate of 0.5-1.5 ℃ / min and pyrolyzed at a constant temperature for 1.5-2 h to obtain the shaped carbon material.
7. The method for preparing composite carbon source-based hard carbon material according to claim 6, characterized in that, The shaped carbon material is heated to 800-850 °C at a heating rate of 2-5 °C / min under an inert atmosphere, and then activated by introducing CO2 with a volume fraction of 55%.
8. The method for preparing composite carbon source-based hard carbon material according to claim 1, characterized in that, Ultra-high temperature deep carbonization treatment involves heating to 1400 ℃ at a heating rate of 1–3 ℃ / min under an inert atmosphere for 2–3 h.
9. A composite carbon-based hard carbon material prepared by the preparation method according to any one of claims 1-8.
10. An application of the composite carbon source-based hard carbon material according to claim 9, characterized in that, Its application as a negative electrode material in sodium-ion batteries.